Caracterização estrutural, vibracional e térmica de microbastões de AgVO3 - MIRANDA, Antonio Werbeson (2023)
In this work we present a study of the structural and phonon properties of silver vanadates in the α-AgVO3 and β-AgVO3 structures. The samples were synthesized by the coprecipitation method and characterized by X-ray Diffraction (XRD), Raman Spectroscopy and Scanning Electron Microscopy (SEM). The α-AgVO3 and β-AgVO3 crystals have rod morphology with micrometric diameter. XRD analyzes together with Rietveld refinement confirmed that the α- AgVO3 sample crystallized in the monoclinic structure of space group C2/c, Z = 8, with the lattice parameters a = 10.4499(8) Å, b = 9, 9256 (5) Å, c = 5.5260 (4) Å, β = 99.647 (8) °, V = 565.07 (7) Å3 , while the β-AgVO3 sample was obtained in the monoclinic structure of space group C1/ m1, Z = 8, with the lattice parameters a = 18.1177 (3) Å, b = 3.58232 (8) Å, c = 8.0389 (2) Å, β = 104.437 (1) °, V = 505.27 (2) Å3 . XRD experiments at low temperatures (298 – 12 K) demonstrated thermal stability of the α-AgVO3 and β-AgVO3 phases and uniaxial negative thermal expansion in the b direction of the β-AgVO3 microcrystals. Raman Spectroscopy and XRD experiments at high temperatures (298 – 673 K) demonstrate that α- AgVO3 microrods exhibit two temperature-induced phase transitions at 413 and 513 K during heating (α → α' → β'), and a transition at 433 K to the β-AgVO3 phase during return to room temperature (β' → β). The β-AgVO3 microrods show a structural transition from the monoclinic phase to a triclinic phase at 473 K (β → β’). The temperature-induced structural modifications in the α-AgVO3 and β-AgVO3 phases, as well as the uniaxial negative thermal expansion in the β-AgVO3 phase are not yet demonstrated in the literature.